Successful Treatment with Afatinib after Osimertinib-induced Interstitial Lung Disease in a Patient with EGFR-mutant Non-small-cell Lung Cancer - Nishima, Shunichi (Intern Med, 2020)
Osimertinib is the standard treatment for epidermal growth factor receptor (EGFR)-mutant non-small-cell lung cancer. However, drug-induced interstitial lung disease (ILD) is recognized as a serious adverse event associated with EGFR-tyrosine kinase inhibitors (TKIs). We herein report a 78-year-old woman with stage IV lung adenocarcinoma harboring an EGFR L858R mutation on exon 21 who received rechallenge treatment with afatinib after osimertinib-induced ILD with an organizing pneumonia pattern. This is the first report of successful rechallenge with afatinib after osimertinib-induced ILD. Treatment with other EGFR-TKIs after osimertinib-induced ILD may be an option for subsequent therapy.